Effectiveness of digital health in improving pregnancy quality among preconception women: A systematic review - Nurleli, Nurleli; Hadju, Veni; Indriasari, Rahayu; Areni, Intan S.; Masni, Masni; Riskyani, Shanti (Narra J, 2025)
Improving nutrition in women prior to conception represents an alternative approach to enhancing the quality of pregnancy. Increased knowledge and self-efficacy among preconception women positively impact changes in health behavior. The rapid development of technology provides an opportunity to implement innovative interventions, including digital health. The aim of this study was to systematically review the efficacy of digital health interventions in modifying the behavior of preconception women. The data were obtained by searching relevant articles published from 2015 to 2023 in electronic databases, including Google Scholar, Science Direct, Web of Science (WoS), Biomed Central, and PubMed. The following keywords were used: "digital health" OR "mobile health" OR "e-health" AND "preconception women" OR "pre-marriage women." Of the 266 studies identified in the search phase, only those that met the inclusion criteria were included in the review. These criteria included 10 articles that assessed the effectiveness of digital health interventions on the behavior change of preconception women. The articles included in this study originated from diverse countries and addressed various digital health interventions. The findings of the review indicated that ten articles reported an increase in pregnant women's knowledge, nine articles demonstrated an enhancement in self-efficacy, and nine articles documented behavioral changes. The behavioral changes observed included the initiation of folic acid consumption before pregnancy, an increase in vegetable and fruit consumption, and a reduction in unhealthy dietary behaviors, such as maintaining a normal weight, smoking cessation, and reduced alcohol consumption. In conclusion, digital health literacy interventions, delivered via web-based platforms or mobile applications, demonstrate effectiveness in promoting positive preconception health behaviors among women, ultimately contributing to improved pregnancy outcomes.